Preliminary fractional factorial design (FFD) study using incorporation of graphene oxide in PVC in mixed matrix membrane to enhance CO2 /CH4 separation - Raj, K. R.; Sunarti, Abd Rahman (IOP Publishing Ltd, 2019)
Mixed matrix membranes (MMMs) comprising of where polyvinyl chloride (PVC) and graphene oxide (GO) were employed in the membrane fabrication in order to improve the membrane characteristics. In this study of gas separation using mixed matrix membrane, gases such as CO2 and CH4 were used. The objectives of this research were to synthesize and develop MMMs PVC/GO, and also to carry out screening to determine best factors condition for membrane to function at high selectivity. The development of MMMs PVC/GO was based on 5 factors. Based on the screening tests, the run which was made up of factors PVC 20%, GO 4%, 1 bar of pressure during gas permeation, NMP solvent, and immersion time of 300s, shows to have the highest selectivity at 26.09 which was above the upper bound lines in the Robeson's Upper bound plot. Fractional Factorial Design (FFD) was applied to study the minimalization of influenced factors during MMMs preparation. Based on the FFD run, the R-squared (R2) was 1.00. Factors that had less impact on the maximum selectivity were the time membrane immersed in water bath (s), and also gas pressure during gas permeation test.